2022
DOI: 10.1111/vox.13262
|View full text |Cite
|
Sign up to set email alerts
|

Baseline assessment findings of the Africa Society for Blood Transfusion Step‐Wise Accreditation Programme in 10 sub‐Saharan African countries, 2016–2018

Abstract: Background and Objectives: The accreditation of blood services promotes continuous quality improvement in blood and transfusion services. The Africa Society for Blood Transfusion (AfSBT) conducted 20 baseline assessments of National Blood Transfusion Services (NBTS) or blood banks as part of the Step-Wise Accreditation Programme (SWAP) in 10 sub-Saharan African (SSA) countries from 2016 to 2018. This paper aims to elucidate the process and findings of the baseline assessments.Materials and Methods: This is a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Further, prior authors have suggested the utility of PRT in various countries in Africa given the high prevalence of transfusion-transmitted infections (TTI), reliance on high-risk donors, and suboptimal testing. [15][16][17] Notably, some institutions reported collecting blood onsite from patients themselves, with many relying on rapid diagnostic tests (RDTs) for infectious disease screening, despite their inadequate sensitivity to particular infectious agents. [18][19][20][21][22][23][24] This high utilization of RDTs, which are generally accepted to not be ideal for TTI testing, [18][19][20][21][22][23][24] is likely secondary to a lack of other feasible options.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prior authors have suggested the utility of PRT in various countries in Africa given the high prevalence of transfusion-transmitted infections (TTI), reliance on high-risk donors, and suboptimal testing. [15][16][17] Notably, some institutions reported collecting blood onsite from patients themselves, with many relying on rapid diagnostic tests (RDTs) for infectious disease screening, despite their inadequate sensitivity to particular infectious agents. [18][19][20][21][22][23][24] This high utilization of RDTs, which are generally accepted to not be ideal for TTI testing, [18][19][20][21][22][23][24] is likely secondary to a lack of other feasible options.…”
Section: Discussionmentioning
confidence: 99%